Revitalisasi Pendidikan Akhlak Mulia dalam Pembentukan Karakter Mahasiswa di Perguruan Tinggi Agama Islam - Tisna Nugraha (Raheema, 2015)
The education of akhlaq in the Islamic University basically has suited the purpose of national education, to create the potential of students in order to be a great human. Furthermore, as a part of the national education system, the Islamic University has a significant role to actualize the function and goal of the national education system. Due to that reason, the Islamic Education curriculum implemented in the Islamic University becomes a compulsory subject of the personality development subjects, especially to create the great humankind (which has al-akhlaq al-karimah) based on strong faith and sharia roles.Moreover, the embed noble character among the students of the Islamic University is important. Besides, the Islamic University is the forefront for the citizen and the other higher education institutions to behave and act in the daily life activities. Therefore, the revived efforts by facilitating and supporting the students in the Islamic University in order the noble character could be realized despite their creativity and intelligence.